The Effect Of Raw Material Quality And Production Process On Product Quality (Survey at Kamiya Home Industry In Rajapolah Sub-District Tasikmalaya District) - Siti Zulfah Syahidah; Suci Putri Lestari; Barin Barlian (Journal of Indonesian Management, 2023)
This study aims to determine the effect simultaneously and partially between Quality of Raw Materials and Production Process on the Product Quality (Survey at Home Industry Kamiya Rajapolah Sub-District Tasikmalaya District). The research method used is a survey method with a quantitative approach. The sampling technique used the saturated sample method with a total sample of 40 peoples. Data collection techniques using online questionnaires. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25. The results show that quality of materials and production process, have a significant effect on performance product quality. Partially, quality of raw materials has a significant effect on product quality. Partially, production process does not have a significant effect on product quality.